Kegiatan Ekstrakurikuler Pramuka di SDN Madyopuro 4 dilihat dari Sudut Pandang Pendidikan Karakter - Chaerisa Nadella Putri (STKIP AL HIKMAH SURABAYA, 2024)
The development of positive character in children today presents a considerable challenge. Scouting extracurricular activities can provide a platform for children to develop positive character traits. This study aims to describe scouting activities at SDN Madyopuro 4 from a character education perspective. The research method used is descriptive qualitative. Scouting activities at SDN Madyopuro 4 serve as a structured means of character education, fostering basic skills and instilling values of religiosity, culture, environmental care, and students’ s.